(3eSchcGJ SQ ef QCi efP JCSjSgG h MJi fgGjI YgO GdNdjaI GdeYJeO Ydi Gddg GdYUQ GdYHGSj GdKGfj (B-221-279(3g``(B/836-892(3e (B: s (3OQGSI CKQjI afjI (B/ s - (3Sdhi ebQf MeO GdfYjejs; (3QCaJ eMeO GdfHQGhj (B: s; (3eMeO MeRI ESeGYjd GdMOGO (B: s ((3GdbGgQI (B: s (3Sdhi ebQf MeO GdfYjej (B: s, 2015)
(3JMJd OQGSI GdeOf GdYQHjI GdESdGejI ecGfg egeg Hjf GdOQGSGJ GdJGQjNjI hGdMVGQjI hGdCKQjI (B. (3eOjfI SQ ef QCi JCNP ecGfg egeg Hjf Jdc GdeOf ef MjK JGQjNgG GdSjGSi Ch GdMVGQi h JJfGhd gPg GdOQGSI GdeOjfI ef MjK GdJCSjS h eQGMd JWhQgG h GdYhGed hQGA GNJjGQgG dJMd HZOGO cYGUeI ddNdGag GdYHGSjI MJi Je JQcgG h GdYhOg Edi HZOGO eQI KGfjI s
(3GdeLdO GdKGfi YHGQI Yf dhMGJs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdBKGQ (B- (3bSe GdCKGQ GdESdGejIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdNdjaI GdeYJUe HGddgs; (3SQ ef QCis; (3eSchcGJs